Microstructure and corrosion analysis of coated bulk nanostructured aluminium alloy 6061 - Nur Anis Nabila, Mokhtar (2024)
Equal Channel Angular Pressing (ECAP) is an improved technique in the metal forming process that imposes a high strain to produce ultra-fine grain structure of metal from coarse grain structure for grain refinement without changing its dimension. In this research, the effect of ECAP on the microstructure, hardness and corrosion properties of the aluminium alloy 6061 (AA6061) is investigated. Subsequently, the impact of nanostructuring of AA6061 on zirconia coating behaviour is evaluated. AA6061 was subjected to ECAP processing at two different channel angles which are 120° and 126°. The ECAP-ed samples then were coated with zirconia coating through sol-gel-assisted dip coating at 3 and 7 layers. The microstructure, hardness and corrosion behaviour of coated and non-coated samples were then evaluated. Hardness test has shown the increment in hardness for coated samples with the highest hardness observed 7layer coated ECAP 126°. The open circuit potential and Tafel curve from potentiodynamic results also indicate the corrosion resistance of ECAP-coated samples has improved. Microstructure evaluation of ECAP samples processed at 126° has finer microstructure compared to samples processed at 120°. ZrO2 coating on the ECAP samples also were observed to be more compact with no cracks observed. Grain refinement due to ECAP processing has been identified as the driving force for the improved mechanical and corrosion properties of the AA6061. The various dislocations and grain boundaries in the UFG substrate provide an accelerated driving force for hydrothermal reaction, promoting the creation of a thicker and more compact ZrO2 coating layer. Such a protective coating layer along with the annealed substrate with fewer crystal defects effectively retards the deterioration of corrosion and consequently maintains mechanical efficiency. This suggests that the ECAP processing was able to interact with zirconia thin film which improves adherent properties, thus improving the hardness and corrosion resistance of the samples.